2011
DOI: 10.1007/s12040-011-0117-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation of uranium in a shallow weathered rock aquifer in southern India

Abstract: Uranium occurs naturally in groundwater and surface water. The objective of this study is to understand the causes for the occurrence of uranium and its spatio-temporal variation in groundwater in a part of Nalgonda district, Andhra Pradesh, south India. Uranium deposits occur in the southeastern part of this area. Groundwater samples were collected from 44 wells every two months from March 2008 to January 2009. The samples were analyzed for pH, ORP and uranium concentration. The uranium concentration in groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Due to poor management, landfills [21,22] and municipal wastewater [23] have been the source of groundwater and soil pollution especially in developing countries. Occurrence of metals in groundwater in areas possessing mineral deposits and associated mining activities are common [24][25][26][27]. Potential risk of heavy metal contamination due to application of fertilisers was reported by many others [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Due to poor management, landfills [21,22] and municipal wastewater [23] have been the source of groundwater and soil pollution especially in developing countries. Occurrence of metals in groundwater in areas possessing mineral deposits and associated mining activities are common [24][25][26][27]. Potential risk of heavy metal contamination due to application of fertilisers was reported by many others [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Uranium concentrations in soil samples of the study area are shown in Table II. The uranium concentration in groundwater in the study area and a part of Nalgonda district, Andhra Pradesh, India, has been reported to be in the range of 0.2 ppb to 68 ppb with a mean of 18.5 ppb (Brindha et al, 2011). The uranium concentration in groundwater changes depending on lithology, degree of weathering and rainfall recharge.…”
Section: Resultsmentioning
confidence: 85%
“…Factor 2 has high positive loadings on Na, K, HCO 3 , and NO 3 with a variance of 13.77 % indicating the leaching of nitrate from fertilizer in agricultural lands to groundwater and thus increases these ions in groundwater (Chidambaram et al 2013) because of the onset of agricultural activity during SWM. U, 222 Rn, and PO 4 has a positive loading on factor 3 with a variance of (Brindha et al 2011). Factor 4 has positive loadings on F with a variance of 8.74 %; it also represented poor positive loadings of pH indicating the dissolution of F in groundwater (Yidana et al 2008b).…”
Section: Swmmentioning
confidence: 97%
“…Factor 3 samples show strong positive loadings of U and 222 Rn with 10 % of total variance which explains the occurrence of U and 222 Rn in groundwater; it may be evolved due to dissolution and leaching of U ions from the weathering process (Brindha et al 2011). Factor 4 samples have strong positive loadings on pH, H 4 SiO 4 , and F with 8.5 % of total variance which illustrates the pH-enhanced dissolution of F due to weathering processes (Manikandan et al 2012).…”
Section: Factor Analysismentioning
confidence: 99%